The Effect of Intellectual Capital, Social Networks, Financial Capital on the Performance of Social Entrepreneurs in West Java - Ramdhan Kurniawan; Titin Endrawati; Rina Destiana; Agus Santoso; Devid Ruung Pontoan (Universitas Nusa Putra, 2023)
This research aims to investigate the influence of intellectual capital, social networks, and financial capital on the performance of social entrepreneurs in West Java, with a sample size of 300. The research adopts a mixed- method research design, which includes qualitative and quantitative phases. The qualitative phase involves conducting in-depth interviews with social entrepreneurs in West Java, while the quantitative phase entails surveying social entrepreneurs in West Java. The research findings indicate that intellectual capital, social networks, and financial capital have a significant impact on the performance of social entrepreneurs. The implications of these findings for social entrepreneurship in West Java are also discussed.